EFFECT OF FOLAIR APPLICATION OF GIBBERELLIN AND NUTRIENTS ON GROWTH AND YIELD OF POTATO VAR. “BURREN” - & Abdul Rasool, Zainaldeen (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this experiment is to investigate the effect of gibberellin and nutrients on growth and yield of potatoes. Factorial experiment (4 × 5) within randomized complete block design with three replications was carried out during two spring seasons (2016 and 2017) on potato plant var. Burren. The experiment for the first season was conducted in the fields of the Ministry of Agriculture while the season was at the fields of Agriculture College University of Baghdad. The experiment included foliar application of gibberellin using different concentrations 0, 50, 100, 200 mg.L-1 and symbolized as GA3(0), GA3(1), GA3(2) and GA3(3), respectively. The second factor was foliar two nutrients compositions separately where the first one was Disper at concentrations 1 and 2 g.L-1 and symbolized as D1 and D2, respectively while the other was Tecamine flower at concentrations 3 and 6 ml.L-1 and symbolized as T1 and T2, respectively in addition to the control treatment which symbolized as C0. Results showed that GA3(3)+D2 increased plant height (71.00 and 77.36 cm. plant-1 for the two seasons, respectively). The highest leaves area during the first season was at GA3(3)+T2 (2,823 m2.plant-1). The highest concentration of chlorophyll was at GA3(3)+T2 (478.9 and 462.6 mg.100 g-1 for the two seasons, respectively). The highest number of tubers was obtained in GA3(3)+ D2(13.2 and 9.21 tuber.plants-1 for the two seasons, respectively). GA3(3)+ T2 gave the highest tuber’s weight during the first season (165.2 g. tuber-1) while the highest plant yield was in GA3(3)+ D2 which reached 2.328 and 1.293 Kg. plant-1 for the two seasons, respectively. Therefore spraying with gibberellin or nutrients improved vegetative growth and increase yield of potato in the spring season for central region of Iraq.